Automatic current-voltage characteristic measurement using transistors as variable load - Bekturhanov, Zh.S.; Kussaikin, S.V. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article describes a method for measuring current-voltage characteristics using transistors as a variable load. Suggested system is part of an automated quality control complex for space applications solar panels. As a part of the description of the system its integral parts are described, both hardware and software. Several examples of calculations and measurements using this system are presented. In conclusion, an opinion on the functionality and performance of the system is provided.
Айнымалы жүктемелер ретінде транзисторларды қолдануы арқылы вольтамперлік сипаттаманы автоматты түрде өлшеу
Автоматическое измерение вольтамперной характеристики с использованием транзисторов в качестве переменной нагрузки
Keywords: current-voltage characteristics; energy generators; solar cells; transistors